Experimental Study on Thermal Sensation of Radiant Cooling Workstation and Desktop Fan in Hot-humid Environment. (2017) - He, De; Li, Nianping; He, Yingdong; He, Meiling; Song, Chunhui; Chen, Haowen
Abstract: This study focuses on thermal sensation of subjects with radiant cooling workstation and desktop fan in hot-humid environment. Twenty-four human subjects participated in the experiments and reported their thermal sensation of the whole body, head, trunk, upper limb and lower limb in hot-humid environment at 26℃, 28℃ and 30℃ in an environmental chamber, respectively. The obtained results show that radiant cooling workstation and desktop fan significantly improved the thermal sensation of subjects in hot-humid environments, but the effect was not obvious at 26℃. The average vote of thermal sensation at 28℃ was between -0.2 and 0, and subjects still had neutral thermal sensation condition although indoor environment was as high as 30℃ while the relative humidity was 80%. Therefore, radiant cooling workstation and desktop fan can extend comfortable temperature range in summer. This study provides a new way for both maintaining comfort in non-neutral environment and saving energy in buildings.